2000
DOI: 10.1093/dnares/7.2.121
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans KLP-11/OSM-3/KAP-1: Orthologs of the Sea Urchin Kinesin-II, and Mouse KIF3A/KIFB/KAP3 Kinesin Complexes

Abstract: Kinesins are intracellular multimeric transport motor proteins that move cellular cargo on microtubule tracks. It has been shown that the sea urchin KRP85/95 holoenzyme associates with a KAP115 non-motor protein, forming a heterotrimeric complex in vitro, called the Kinesin-II. Here we describe isolation of a cDNA clone corresponding to the klp-11 kinesin in C. elegans. Our sequence analysis of the encoded KLP-11 shows that it shares high homology with the OSM-3 kinesin. We also describe a nematode cDNA encodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
1
6
1
Order By: Relevance
“…elegans KLP-11 mediates IFT in the proximal cilia region [ 44 ]. In contrast to our data with OSM-3, phosphorylated Fla8 (Fla8-S663D) inhibits entry of kinesin-II in the cilia, whereas unphosphorylated Fla8 (FLA8-S663A) stimulates entry [ 28 , 41 ]. Kinesin 2a (Kif2a) has recently been shown to localize to the basal body at the base of the cilium when it is not involved in the cell cycle, and when phosphorylated by another ciliary kinase, Polo-like Kinase 1, becomes activated–showing a similar behavior as we observe for OSM-3.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…elegans KLP-11 mediates IFT in the proximal cilia region [ 44 ]. In contrast to our data with OSM-3, phosphorylated Fla8 (Fla8-S663D) inhibits entry of kinesin-II in the cilia, whereas unphosphorylated Fla8 (FLA8-S663A) stimulates entry [ 28 , 41 ]. Kinesin 2a (Kif2a) has recently been shown to localize to the basal body at the base of the cilium when it is not involved in the cell cycle, and when phosphorylated by another ciliary kinase, Polo-like Kinase 1, becomes activated–showing a similar behavior as we observe for OSM-3.…”
Section: Discussioncontrasting
confidence: 99%
“…Ultra-structural analysis of the cilia in nphp-4(tm925);osm-3(yhw66) mutants by transmission electron microscopy (TEM) confirms that the double mutant cilia lack distal segments while maintaining normally formed middle segments ( Fig 3E ). This is similar to what is seen in osm-3(mn357) null mutants [ 28 , 29 , 34 ]. Osm-3(yhw66) single mutants were also analyzed; and have properly formed distal segments ( Fig 3E ).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Initially OSM-3 was thought to be a subunit of a heterotrimeric kinesin-II (Wedaman et al 1996, Cole et al 1998, Khan et al 2000, but careful fractionation experiments showed that it is a subunit of a distinct homodimeric complex, whose two N-terminal motor domains are predicted to be linked by a 26-nm coiled-coil rod to a short tail (Signor et al 1999b). Perhaps, homodimeric kinesin-II transports a cargo distinct from that transported by heterotrimeric kinesin-II, but the functional relationship between these motors is unknown.…”
Section: Scholeymentioning
confidence: 99%
“…This was not necessarily expected because some lower organisms are known to have two distinct kinesin‐II complexes operating in their cilia. The best characterized of these is Caenorhabditis elegans where CeKRP85, CeKRP95 and CeKAP combine to form a heterotrimeric complex analogous to the Chlamydomonas FLA10/FLA10H/CrKAP complex (39,40). C. elegans also expresses OSM‐3 (41), a third kinesin‐II motor protein, which is required for ciliary assembly (42) and appears to homodimerize with itself but does not associate with CeKRP85, CeKRP95 or CeKAP (39).…”
Section: Kinesin‐iimentioning
confidence: 99%